Conservational Exploitation as a Sustainable Development Strategy for a Small Township: The Example of Waipu District in Taichung, Taiwan - Li-Wei Liu; Pei-Yin Ko (Journal of Urban Management, 2014)
ABSTRACT: The contemporary form of urban-rural interfaces is moving toward a more hybridized identity, since nowadays ambiguous places prevail. In particular, contemporary rural settlements are increasingly exhibiting urban characteristics in terms of their built environments. Many traditional agricultural landscapes in the world have thus been altered due to rapid urbanization, such that in order to maintain environmental diversity, the conservation of agricultural landscapes and their functions has become an important issue. Waipu District is located in the northwest of Taichung, a peri-urban area of Taichung City. This means that Waipu is rural in appearance at present but may undergo rapid urbanization in the near future. In order to protect quality local characteristics from land exploitation and move towards sustainable development, this paper depicts a strategy of conservational exploitation which is adopted to direct the future development of Waipu so as to maintain its characteristics and environmental sustainability. This paper also briefly documents the process of an experimental practice through which graduate students with landscape architecture, recreation, and urban planning backgrounds have taken part in an experimental project with professional social services in order to develop master plans for Waipu. By means of field surveys, interviews with local people, and discussions with local officials, a landscape master plan, a tourism plan, and a spatial plan developed by the students have been provided to the Waipu District Office. These plans are intended to help Waipu to develop its unique characteristics, improve local landscapes, and promote local economic development. In order to conserve rural landscapes, cultural landscaping and cultural tourism have been identified as development concepts for future development. Conservational exploitation which focuses on maintaining cultural landscapes and promoting cultural tourism can serve as the overall development strategy. KEYWORDS: Conservational exploitation, cultural landscape, rural tourism, Waipu District of Taichung